Wrongdoing in Publicly Listed Family- and Nonfamily-Owned Firms: A Behavioral Perspective. (July 2023) - Smulowitz, Stephen J.; Cossin, Didier; De Massis, Alfredo; Lu, Hongze (Abraham)
We integrate research on family-owned firms (FOFs) and the Behavioral Theory of the Firm (BTOF) to study wrongdoing—a specific dimension of corporate social responsibility (CSR) associated with destructive risk—in family- versus nonfamily-owned firms (NFOFs). We argue that FOFs are likely to respond differently from NFOFs to risks because in addition to concern for economic costs and benefits, FOFs are uniquely concerned with the socioemotional wealth (SEW) accruing from the noneconomic costs and benefits of their actions. Furthermore, we argue that the differences in behavior are dependent upon whether the nature of risk associated with a behavior is destructive, as in the case of wrongdoing, versus productive, as in the case of other previously examined behaviors such as research and development [R&D] investment, diversification, or internationalization. Our analyses, based on 17, 022 observations from a sample of 1, 900 publicly traded U.S. firms from 1999 to 2016, provide robust empirical support for these predictions, showing that FOFs commit less wrongdoing than their nonfamily counterparts and respond to performance relative to aspirations regarding wrongdoing in a way that varies from their responses regarding other behaviors examined in prior studies. We thereby advance the literatures on BTOF and FOFs by explaining how family owners' decisions change depending on the type of risk associated with their behavior— destructive versus productive, and by integrating the additional aspiration related to SEW into BTOF predictions to tell a more complete story of organizational wrongdoing from the BTOF perspective. By focusing on wrongdoing as a specific dimension of CSR, our findings also have implications for CSR research as they show that the relative importance of social responsibilities shifts according to the type of risks (and trade-offs) associated with those responsibilities.